The effect of school leaders' feedback on teaching quality perceived by students – results of an intervention study. Issue 1 (2nd January 2023) - Kellermann, Christopher; Nachbauer, Max; Gaertner, Holger; Thiel, Felicitas
ABSTRACT: Feedback from school leaders often is of low quality and not always effective. Because school leaders spend only limited time on instructional leadership activities, an intervention was developed to assist them in efficiently providing high-quality feedback to teachers. The effectiveness of the intervention was evaluated within a quasi-experimental study. N  = 11 school leaders were trained in conducting classroom observations and providing feedback. School leaders observed teachers of the intervention group ( N  = 26) and provided feedback with regard to 14 teaching characteristics. N  = 27 teachers served as a control group. It is examined whether the intervention leads to improvements in teaching quality perceived by students. Multilevel regression analyses were conducted. For three of the 14 teaching characteristics, intervention group students ( N  = 518) rated changes in teaching quality significantly better than control group students ( N  = 551). The results provide first evidence for the effectiveness of the intervention.